Managing the Sustainable Development of the Enterprise on the basis of the Vulnerability Level (Marketing i Menedžment Innovacij)
The concept of sustainable development for both enterprises and nations involves the integration of the principles of systematicity, complexity, and balance in the development of all three components: economic, social, and environmental. The primary goal of this research is to develop a management strategy for enterprise sustainable development on the basis of an algorithm for the comprehensive assessment of the vulnerability levels of individual indicators within the three components of sustainable development. This paper reviews the stages of the evolution of the sustainable development concept, presenting arguments and counterarguments within the scientific debate on the systematisation of the 169 targets of the SDGs into a three-component model that combines economic, environmental, and social elements. The systematisation of literature sources and approaches to addressing the issue of balancing the components of sustainable development has shown that resolving this challenge will contribute to the formation of a sustainable economy, environmental sustainability, and social justice. The urgency of solving this scientific problem arises from the fact that, under martial law in Ukraine, determining the most vulnerable indicators by components – to protect them and create conditions for their preservation and further development – is of paramount importance. The assessment of the vulnerability levels of indicators across the components of sustainable development was conducted in a logical sequence, following ten clearly defined stages. The methodological framework of the research centres on justifying the use of the adapted CARVER matrix to build a system for ranking the vulnerability of individual indicators within the components of sustainable development. To illustrate the proposed methodological approach, an assessment of the vulnerability levels of sustainable development indicators was conducted via the example of a hypothetical enterprise. This study empirically confirms and theoretically substantiates the need to determine the qualitative characteristics of the vulnerability levels of indicators across the components of sustainable development, with gradations into low, medium, increased, and high vulnerability. The results of the conducted research can be useful for enterprise managers in ranking the vulnerability of individual indicators across the components of sustainable development via the adapted CARVER matrix. This approach also enhances their ability to respond promptly to changes, not only within the components of sustainable development but also in their individual indicators.